Benin : 2008 Article IV Consultation and Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Augmentation of Access - Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Benin. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that in the last two years, Benin has experienced a pickup in growth and low inflation supported by prudent fiscal policies and external debt relief. However, progress in addressing core economic vulnerabilities has fallen short of expectations, and the external environment has become less favorable with a strengthening CFA franc adding to competitiveness concerns and surging food and fuel prices accentuating a deterioration in the terms of trade. The surplus on the narrowly defined primary budget is projected to decline to 0.5 percent of GDP in 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet